Role of heat shock proteins in the exercise response - Fehrenbach, E.; Niess, A. M. (Exercise Immunology Review, 1999)
Heat shock proteins (HSP) are a characteristic set of highly conserved proteins that are synthesized shortly after the organism is exposed to external stress, including physical activity. HSP help to maintain cellular homeostasis and protein conformation, reactivate denatured or malformed proteins, and provide Òhousekeeping,Ó translocase, and chaperone functions. Some of the conditions known to elicit the cellular stress reaction are similar to those experienced by cells in response to physical exercise. Hyperthermia, ischemia, oxidative, cytokine and muscular stress, glucose deprivation, and alterations in calcium and pH are potent inducers of HSP expression in different types of cells and tissues. This review provides an overview of the cellular heat shock response to exercise. The presently known exercise related HSP are introduced. Their possible roles in response to acute exercise, thermotolerance, adaptation to training, aging, and immunological reactions are discussed.